Differential Accumulation: Toward a New Political Economy of Capital - Jonathan Nitzan (Review of International Political Economy, 1998)
Existing theories of capital, neo-classical as well as Marxist, are anchored in the material sphere of production and consumption. This article offers a new analytical framework for capital as a crystallization of power. The relative nature of power requires accumulation to be measured in differential, not absolute, terms. For absentee owners, the main goal is not to maximize pro.ts, but rather to “beat the average” and exceed the “normal rate of return”. The theoretical framework builds on Thorstein Veblen's separation of industry from business and on Lewis Mumford's dichotomy between democratic and authoritarian techniques. Extending their contributions, we argue that capital is a business, not an industrial category, a human mega-machine rather than a material artefact. Indeed, it is the social essence of capital which makes accumulation possible in the .rst place. Capital measures the present value of future business earnings, and these depend not on the productivity of industry as such, but on the ability of absentee owners strategically to limit such productivity to their own differential ends. Introducing the twin concepts of the “differential power of capital” (DPK) and the rate of “differential accumulation” (DA), we examine the non-linear and possibly negative link between industrial growth and accumulation in the USA.
Keywords: 330; accumulation; capital; capitalism; centralization; competition; conflict; conglomeration; corporation; credit; crisis; debt; development; distribution; dual economy; elite; finance; institutionalism; Marxism; methodology; Mumford; ownership; Palestine; po